Studi literatur: Dampak Kompensasi dan Motivasi terhadap Kinerja Karyawan di Perusahaan - Atikah, Resni; Taufiqurahman, Endang (Al-Maqashid: Journal of Economics and Islamic Business, 2025)
In achieving quality productivity, the role of human resources is crucial in assessing their ability to adapt to the times, which are full of innovation and fierce competition between companies. The purpose of this study is to determine the impact of compensation, motivation, and job satisfaction on employee performance in companies. This study employs a qualitative method with a literature review approach, utilizing academic sources such as Mendeley and Google Scholar. The findings reveal that compensation has a positive impact on employee performance. Additionally, motivation was found to have a positive effect on employee performance. Similarly, job satisfaction was also found to have a positive impact on employee performance.